PELATIHAN PENGENALAN DIGITAL MARKETING PEMASARAN PRODUK PERTANIAN DI KELURAHAN KALI ABANG TENGAH - Septiana Ningtyas; Rizky Tri Asmono; Lela Nurlaela; Ike Kurniati; Jelman Nasri (Institut Teknologi dan Bisnis Swadharma, 2023)
The digital era has touched almost all aspects of life in various fields. No exception, farmer have to responsive in utilizing technology. Indonesia is an agricultural country with many agricultural products but has a problem with the price of agricultural products that are not commensurate with the needs of basic materials. The low selling price at the farm level is due to the length of the distribution chain and the large number of trading institutions involved in the distribution process so the selling price of the final consumer is quite high. Millennial farmers in Kali Abang Tengah Village have the hope of developing young agricultural entrepreneurship. The potential of millennial farmers is the goal of ITB Swadharma's community service this time. By introducing digital marketing to millennial farmers, farmers can directly connect to costumers at a market price. The results achieved in the extension activities on digital marketing for marketing agricultural products went smoothly and provided benefits to the target audience, namely millennial farmers in the Kelurahan Kali Abang Tengah.Memasuki Era digital dalam berbagai bidang yang penggunaannya telah menyentuh hampir seluruh aspek kehidupan. Tidak terkecuali pebisnis di bidang pertanian harus tanggap dalam memanfaatkan teknologi. Indonesia sebagai negara agraris dengan berbagai produk pertanian, tetapi memiliki permasalahan dangan harga produk pertanian yang tidak sepadan dengan kebutuhan bahan bahan pokok. Rendahnya harga jual di tingkat petani akibat panjangnya rantai distribusi dan banyaknya lembaga tataniaga yang terlibat dalam proses distribusi sehingga harga jual konsumen akhir cukup tinggi. Para petani milenial Kelurahan Kali Abang Tengah menjadi harapan dalam mengembangkan kewirausahaan muda pertanian. Adanya potensi petani milenial menjadi tujuan pengabdian masyarakat ITB swadharma kali ini. Dengan memperkenalkan digital marketing kepada petani milenial dapat menghubungkan secara langsung petani kepada konsumen, dengan harga yang lebih tinggi tentunya. Hasil yang dicapai dalam Kegiatan penyuluhan tentang digital marketing untuk pemasaran produk pertanian berjalan lancar dan memberikan manfaat kepada khalayak sasaran yaitu petani milenial Kelurahan Kali Abang Tengah.